desencapados - Costa, Felipe Marcondes da (Revista do Colóquio, 2020)
The reseach of "Desencapados" consists of exploring the tension between verbal text and writing support, which is no longer a blank sheet or a canvas and turns into a series of documents that concern the author. Thus, the relationship between the pre-existing support and the poetic discourse that is written above is placed at the foreground, in order to establish tensions between formal statements and thematic statements. It is the contradiction that makes the organism alive. In this case, the presence of poems by other authors written by hand in protocol papers, in a performance action, operates as an ironic displacement.
Keywords: hybrid arts; visual arts; contemporary poetry; interdisciplinary project; art of performance